New Possibilities of Hybrid Texture of Neutrino Mass Matrix - Madan Singh (Advances in High Energy Physics)
We investigate the novel possibilities of hybrid textures comprising a vanishing minor (or element) and two equal elements (or cofactors) in light neutrino mass matrix Mν. Such type of texture structures leads to sixty phenomenological cases each, out of which only fifty-six are viable with texture containing a vanishing minor and an equality between the elements in Mν, while fifty are found to be viable with texture containing a vanishing element and an equality of cofactors in Mν under the current experimental test at 3σ confidence level. Detailed numerical analysis of all the possible cases has been presented.